The Role of Digital Health Literacy in Optimizing Telemedicine and e-Health Applications for Healthcare Accessibility - Falaah, Fathi (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2024)
The rapid advancement of e-Health applications has transformed medical information seeking behavior, offering new opportunities for improved healthcare accessibility and patient empowerment. This study systematically reviews the impact of e-Health applications on online medical information seeking behavior, focusing on accessibility, credibility, and user engagement. A comprehensive literature review was conducted using major academic databases, including PubMed, Scopus, and Google Scholar. The findings reveal a substantial increase in the use of digital health platforms, with telemedicine and mobile-Health applications becoming primary sources of medical information. However, concerns regarding digital literacy, misinformation, and data privacy persist. The study highlights the need for enhanced regulatory frameworks, greater involvement of healthcare professionals in e-Health development, and the implementation of educational initiatives to improve-Health literacy. The integration of e-Health applications into national healthcare policies is recommended to optimize their effectiveness and accessibility. Future research should focus on evaluating the long term impacts of e-Health solutions and their role in addressing health disparities. This study contributes to the growing discourse on digital health by emphasizing the importance of policy development and education in maximizing the benefits of e-Health applications.